Enhancing sustainable development through implementing complex adaptive systems and reflection: A proposed framework - Naude, Marita (Virtus Interpress, 2013)
Most organizations regard Sustainable Development (SD) as important and within a tridimensional approach (including economic, social and environmental dimensions) SD comprises a range of complex issues. However, traditional management approaches do not capture the variabilities as organizations are complex adaptive systems embedded in a complex adaptive context. Consequently, there must be a fundamental shift towards a complexity theory approach (eg. Complex AdaptiveSystems, CAS). When SD is viewed from a CAS approach it becomes a continuous process of coevolution within a rapidly changing context rather than a once off project. Leaders, managers and practitioners work in this complex and rapidly shifting world need crucial skills such as reflection. This paper proposes a framework combining SD, CAS and reflection. Although a framework does not guarantee success it provides a tool to identify SD, CAS and reflection dimensions, develop an integrated approach, create goals, monitor and evaluate outcomes. Lastly, the paper includes management and research implications.